Gene Flow Between the Wild Rice Species (Oryza longistaminata) and Two Varieties of Cultivated Rice (Oryza sativa) in Kilombero District, Tanzania - Mangosongo, Hashim M.; Mneney, Emmarold E.; Wanjala, Bramwel (Tanzania Journal of Science, 2024)
The direction and rate of gene flow between the perennial wild rice species, O. longistaminata and cultivated rice, O. sativa was investigated using nine Microsatellite (SSR) markers. The study involved characterization of parental lines of two cultivated rice varieties and O. longistaminata and their F1 progenies. Presence of crop-specific alleles in the wild species or vice-versa was used as an indicator of occurrence of gene flow between the two species. The study revealed that gene flow between O. longistaminata and each of the two varieties of O. sativa occurs naturally. The direction of gene flow was mainly from the cultivated to wild species. The rate (frequency) of gene flow was higher from cultivated (O. sativa) to wild rice (O. longistaminata) than from O. longistaminata to O. sativa and varied with cultivated rice variety. Higher rate of gene flow from cultivated to wild species could be due to floral structure and out-crossing nature of the wild species (O. longistaminata). Gene flow between O. longistaminata and O. sativa is likely to change genetic integrity of natural populations of the two species in areas where they occur sympatrically. However, isolation by distance can help to control gene flow between these species.